2021
DOI: 10.3389/fmicb.2021.765691
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Ileum Microbiota Composition in Piglets at Different Growth Stages

Abstract: Intestinal microbiota can affect the intake, storage, and absorption of nutrients in the body, thereby greatly impacting the growth and development of animals. In addition to diet, the breed and growth stages of pigs could also affect changes in the intestinal microbiota. However, research on the developmental changes in the ileum microbiota of piglets remains unclear. In this study, the ileum microbiota of Jinfen White and Mashen piglets at different developmental stages were investigated using 16S rRNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…There is evidence that Firmicutes are efficient producers of butyrate 38 . Firmicutes are the most abundant bacteria inhabiting the gut and play a role in the metabolism of energy from the host, which may lead to increased fat accumulation in pigs, as proposed by others 39,40 , but this was not evaluated in the present work. Interestingly, the proportion of Actinobacteriota was abundant in the combined treatment of 40% HA-starch and 40%CPCC group and the individual treatment group of 40%HA-starch.…”
Section: Discussionmentioning
confidence: 89%
“…There is evidence that Firmicutes are efficient producers of butyrate 38 . Firmicutes are the most abundant bacteria inhabiting the gut and play a role in the metabolism of energy from the host, which may lead to increased fat accumulation in pigs, as proposed by others 39,40 , but this was not evaluated in the present work. Interestingly, the proportion of Actinobacteriota was abundant in the combined treatment of 40% HA-starch and 40%CPCC group and the individual treatment group of 40%HA-starch.…”
Section: Discussionmentioning
confidence: 89%
“…The present study found that the addition of 0.05% tributyrin increased the GE and fat digestibility of lactating sow. This shows that tributyrin supplementation can effectively regulate the intestinal microbial community to affect nutrient digestibility, thus greatly influencing the growth and development of animals ( Lu et al, 2021 ). In our study, the TB group decreased predicted functions“Nitrate_respiration,” which is related to aerobic respiration, were observed in the sows.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of intestinal microbial diversity, in humans, alpha diversity gradually increases with growth and development before the age of 5 years; however, there is a decrease in gut microbial diversity from 18 to 80 years of age ( 26 , 27 ). Some investigators studied the intestinal flora of pigs on days 1, 28, and 70 and found that with the increase of age, the microbial diversity of the ileum increased, the proportion of Firmicutes increased, and the proportion of Proteobacteria decreased in Jinfen white pigs and Mashen pigs ( 28 ). Microbial diversity tends to increase in chicken embryos up to week 4, peaking at approximately days 14 and 28 for the foregut and hindgut, respectively, and then remaining stable or decreasing slightly thereafter ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%